Association between vitamin D and cholesterol in post-acne hypertrophic scars and keloids: A cross-sectional study - Kurniawati, Yuli; Yahya, Yulia Farida; Diba, Sarah; Novriani, Rina; Yusuf, Hasbiallah; Martgaredta, Ekta (UI Scholars Hub, 2025)
Background: Post-acne hypertrophic scars and keloids result from abnormal wound healing within the pilosebaceous unit. Ruptured microcomedones create wounds that can lead to prolonged inflammation, increased collagen synthesis, and fibrinolysis inhibition, resulting in elevated scar tissue in acne lesions. Vitamin D deficiency can lead to prolonged inflammation and damage to dermal collagen. High total cholesterol levels can lead to excessive sebum production, exacerbating inflammation and fibrosis. This study aimed to determine the association between serum vitamin D and total cholesterol levels with scar severity in patients with post-acne hypertrophic scars and keloids. Methods: This analytical cross-sectional study was conducted at Dr. Mohammad Hoesin General Hospital, Palembang, South Sumatera, Indonesia, among patients who met the inclusion and exclusion criteria. Scar severity was assessed using the Vancouver Scar Scale (VSS). Blood samples were collected for examination of serum vitamin D and total cholesterol. The data were analyzed statistically. Results: Chi-square test of serum vitamin D with VSS scores showed a significant association (p-value = 0.007), while total cholesterol with VSS showed no association (p-value = 1.000). Odd-ratio (OR) for serum vitamin D and VSS was 60, concluding that vitamin D deficiency increased the risk of high VSS by 60-fold in study patients. Conclusion: There was a significant association between serum vitamin D levels and VSS score, while there was no association between total cholesterol and VSS score. Deficiency of serum vitamin D is associated with a higher risk of developing a higher VSS score in patients with post-acne hypertrophic scars and keloids.